2009
DOI: 10.1111/j.1558-5646.2009.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-Dependent Native Habitat Preference Facilitates Divergence Between Parapatric Lake and Stream Stickleback

Abstract: Adaptive divergence between adjoining populations reflects a balance between the diversifying effect of divergent selection and the potentially homogenizing effect of gene flow. In most models of migration-selection balance, gene flow is assumed to reflect individuals' inherent capacity to disperse, without regard to the match between individuals' phenotypes and the available habitats. However, habitat preferences can reduce dispersal between contrasting habitats, thereby alleviating migration load and facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
199
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(207 citation statements)
references
References 92 publications
(136 reference statements)
7
199
1
Order By: Relevance
“…Although stream -lake fish in the current study differ in dorsal and pelvic spine lengths, none of the outlier regions we identified map near the previously described QTLs. By contrast, variation in body depth has been linked to a QTL (marker: Stn321) in another cross between marine and freshwater sticklebacks [42], and this marker has been shown to be highly differentiated between a stream -lake stickleback pair using a candidate marker approach [37]. The body depth Stn321 QTL marker is located on Chr7 at approximately 13.66 Mb [42], approximately 450 kb from an SNP, we identified as an outlier in the Mayer and Drizzle systems.…”
Section: Discussion (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although stream -lake fish in the current study differ in dorsal and pelvic spine lengths, none of the outlier regions we identified map near the previously described QTLs. By contrast, variation in body depth has been linked to a QTL (marker: Stn321) in another cross between marine and freshwater sticklebacks [42], and this marker has been shown to be highly differentiated between a stream -lake stickleback pair using a candidate marker approach [37]. The body depth Stn321 QTL marker is located on Chr7 at approximately 13.66 Mb [42], approximately 450 kb from an SNP, we identified as an outlier in the Mayer and Drizzle systems.…”
Section: Discussion (A)mentioning
confidence: 99%
“…In the Drizzle and Mayer systems (where we sampled multiple streams), stream-form fish are generally more genetically similar to each other than to lake fish, and this is a genome-wide effect that persists when outlier loci are removed. This indicates continued gene flow through the lake, perhaps facilitated by phenotype-dependent habitat preferences [37]. Why the 'benthic' stream-forms do not become established in these lakes is an intriguing question and remains a topic for future ecological investigations.…”
Section: Discussion (A)mentioning
confidence: 99%
“…Therefore, non-random gene flow is a distinct evolutionary force capable of driving adaptive evolution, in addition to natural selection. mating and allowing genetic divergence to build up between populations just tens of meters apart [15]. Habitat imprinting and host plant preferences are also widely invoked to explain speciation in phytophagous insects [31,67].…”
Section: Speciationmentioning
confidence: 99%
“…However, it is becoming increasingly clear that gene flow can have a far more complex role in evolution than generally believed [12][13][14][15][16]. Thus, it is time for a substantial rethinking of the emphasis of evolutionary theory on the…”
mentioning
confidence: 99%
“…However, as pointed out by Edelaar and Bolnick (2012), gene flow can play a much more complex role. Nonrandom genotype-dependent dispersal appears naturally in numerous organisms, e.g., aquatic species (Lutscher et al 2007;Bolnick et al 2009), butterflies (Haag et al 2005;Hanski et al 2006), and plants that are polymorphic in flower shape and/or color (Stanton 1987). Thus, the question arises about the impact of genotype-dependent dispersal on processes of natural selection in spatially extended populations.…”
mentioning
confidence: 99%